METODE PEMBELAJARAN AKTIF DALAM MENINGKATAN KEMAMPUAN BERFIKIR KRITIS SISWA DI MI DARUL ULUM AL MUSTHOFA - Zainul Musthofa; Firdaus Ainul Yakin; Nur Fitri Amalia (Jurnal Al-Fatih, 2025)
This study aims to explore the application of active learning methods, specifically the Think-Pair-Share model, in improving students' critical thinking skills at MI Darul Ulum Al Musthofa. Active learning is expected to encourage students to be more involved in the learning process and develop critical thinking skills needed in everyday life. The method used is a qualitative approach with interviews, observation, and documentation as data collection techniques. The results of the study indicate that the implementation of cooperative learning through the Think-Pair-Share model is effective in improving students' participation and critical thinking skills. Students are more active in discussions, asking questions, and expressing their opinions. However, there are challenges in terms of differences in student confidence levels, where some students who are more shy tend to be reluctant to participate in group discussions. Teachers as facilitators play an important role in creating an inclusive learning environment and supporting students to be more confident. These findings indicate that active learning, especially cooperative learning, can enrich students' social and cognitive skills, while contributing to the development of active learning theories that are more responsive to students' individual needs.